A New Polymorph of Potassium Chromate(III), β‐KCrO2, and Reinvestigation of α‐KCrO21. Issue 2 (27th November 2012) - Zafar Ali, Naveed; Nuss, Jürgen; Jansen, Martin
Abstract α‐KCrO2 was synthesized by the azide/nitrate route. Stoichiometric mixtures of the precursors (KN3, KNO3, and Cr2O3) were heated in a special regime up to 853 K and annealed at this temperature for 5 h in a specially designed silver container. Dark green single crystals of β‐KCrO2 were grown by post annealing the reaction product at 773 K for 200 h in silver crucibles. According to single‐crystal X‐ray analysis, the new high temperature modification, β‐KCrO2, crystallizes in the β‐RbScO2 type of structure [P63/mmc; a = 3.0427(4) Å, c = 11.924(2) Å; c/a = 3.918; Z = 2]. The characteristic feature of the structure are CdCl2 analogue slabs of [CrO6/3]– edge shared octahedra stacked along the [001] direction with K+ atoms incorporated between the layers in a trigonal prismatic arrangement, rare for lighter alkali atoms. We have reinvestigated the specific heat (from 2 to 300 K) and the magnetic susceptibility (2 to 350 K) on α‐KCrO2, and clearly identified in the specific heat measurements, a λ‐type anomaly at 23 K, indicating the onset of long‐range AFM ordering. The Curie‐Weiss fit of experimental data in the temperature range above 100 K, yields the negative Curie‐Weiss temperature of –220 K, indicating predominant antiferromagnetic spin‐exchange interaction, with an effective magnetic moment (μeff) of the order of 3.91 μB, corresponding to a g‐factor [μeff /μB = g[S(S+1)]1/2] of 2.019 well in accordance for Cr3+ (d3 system) with spin S = 3/2.